2018
DOI: 10.1017/s0950268818003217
|View full text |Cite
|
Sign up to set email alerts
|

The use of capture-recapture methods to provide better estimates of the burden of norovirus outbreaks from seafood in England, 2004–2011

Abstract: Norovirus (NoV) is the greatest cause of infectious intestinal disease in the UK. The burden associated with foodborne outbreaks is underestimated in part because data are dispersed across different organisations. Each looks at outbreaks through a different lens. To estimate the burden of NoV from seafood including shellfish we used a capture-recapture technique using datasets from three different organisations currently involved in collecting information on outbreaks. The number of outbreaks of NoV related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…By comparison, in a C-R study of norovirus cases, the combined databases yielded incidence at a rate 2.5 times the level of the rate of the highest individual database. 9 Moreover, in the current study, the overlap between databases was large, resulting in high disease coverage estimates.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…By comparison, in a C-R study of norovirus cases, the combined databases yielded incidence at a rate 2.5 times the level of the rate of the highest individual database. 9 Moreover, in the current study, the overlap between databases was large, resulting in high disease coverage estimates.…”
Section: Discussionmentioning
confidence: 77%
“…C-R has been adapted from ecological studies and used in a wide array of health-related studies including Alzheimer's disease, heart attack, HIV infection, gun injury, pediatric disease surveillance, gastric cancer, and norovirus infections. [4][5][6][7][8][9] Direct C-R uses two databases and is believed to result in better estimates than indirect C-R, which uses three or more databases. In this study, estimates were nearly identical between observed and estimated incidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study used C‐R methods to calculate influenza incidence among hospitalized patients and then used two methods for population burden: CDC's HAIVEN burden estimate methods and a combination of HAIVEN and C‐R estimates. C‐R has been adapted from ecological studies and used in a wide array of health‐related studies including Alzheimer's disease, heart attack, HIV infection, gun injury, pediatric disease surveillance, gastric cancer, and norovirus infections 7–12 . The Petersen C‐R method using two sources of data in this study is a special case of the generalized C‐R method for estimating burden using multiple data sources.…”
Section: Discussionmentioning
confidence: 99%